2021
DOI: 10.14202/vetworld.2021.3111-3118
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, income, and environmental characteristics of individuals displaying animal and object hoarding behavior in a major city in South Brazil: A cross-sectional study

Abstract: Background and Aim: Hoarding cases have not been researched in depth in developing countries, such as Brazil. This study aimed to describe the characteristics of people with hoarding behavior in Curitiba, Brazil. Materials and Methods: A cross-sectional study was conducted based on complaints about hoarding situations received by the City Hall. The data on sociodemographic, income, and environmental characteristics of individuals displaying animal and object hoarding behavior were obtained and analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, negative results for individuals with AHD may indicate that B. canis has the lowest zoonotic potential in the genus Brucella [12,17]. Nonetheless, seropositive dogs in close and continuous contact with owners with AHD, mostly elderly, unassisted (last medical visit over 6 months prior), lonely and with comorbidities [1,6], may be a tragic combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, negative results for individuals with AHD may indicate that B. canis has the lowest zoonotic potential in the genus Brucella [12,17]. Nonetheless, seropositive dogs in close and continuous contact with owners with AHD, mostly elderly, unassisted (last medical visit over 6 months prior), lonely and with comorbidities [1,6], may be a tragic combination.…”
Section: Discussionmentioning
confidence: 99%
“…Animal hoarding disorder (AHD) is defined as a psychiatric obsessive-compulsive condition characterized by the accumulation of animals in households, frequently in high numbers and confined to small spaces and lacking minimum nutrition, physical space, sanitation, and veterinary assistance [1,2]. Individuals with AHD often live in unsanitary conditions, leading to vector proliferation and pathogen spread, particularly of zoonotic diseases [1,[3][4][5][6]. In addition, such individuals often fail to recognize animal suffering, are often hungry, trapped, crowded, or even die [1], as indicated by case reports of dogs scavenging the owner's remains [7].…”
Section: Introductionmentioning
confidence: 99%
“…As animal and/or object hoarding disorder has been considered a major sanitary problem worldwide, no contact or mapping attempt by a given municipality was considered a negative indicator of human and animal health and welfare. Such an assumption was based on a recent study by our research group that found a high presence of animal and object hoarding disorder in Curitiba ( 9 ), which has been statistically associated with human and animal cruelty and unsanitary conditions ( 10 ). High identification of hoarders happened in municipalities with higher income and a composite of higher distance from the state capital and higher income.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of animal/object hoarding cases in Curitiba, Brazil, was recently estimated at 1 per 15,500 (6.45 cases per 100,000) inhabitants ( 9 ), which was seen more frequently in women, who were more prone to animal hoarding behavior. The same study also reported that risk factors associated with hoarder behavior have included the proliferation of pests and vectors, risk of fire (e.g., bare wiring or no available electricity leading to the use of candles), and landslips (e.g., object stacking and accumulation falling over persons and animals) ( 10 ). Protection programs and population management of companion animals have been increasingly established by non- and governmental agencies worldwide, mostly performing neutering-spaying services, responsible guardianship programs, animal cruelty surveillance, and adoption of stray, abandoned, and relinquished pets ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of complications due to the individuals age would worsen the already existing mental problems leading to degenerating human, animal, and environmental conditions ( 6 ). Animal hoarders are also more likely to be women living alone (63.8%) with low self-hygiene (65.2%) ( 7 ). Such a scenario creates the optimum conditions for disasters, including accidents such as tripping, falling, and fire; disability, diseases, and health risks due to poor sanitary conditions; and fatal outcomes in severe situations ( 8 ).…”
Section: Introductionmentioning
confidence: 99%